Current topics in artificial intelligence : 13th Conference of the Spanish Association for Artificial Intelligence, CAEPIA 2009, Seville, Spain, November 9-13, 2009 : selected papers - CAEPIA; Meseguer, Pedro; Mandow, Lawrence; Gasca, Rafael M. (Lecture Notes in Computer Science, 2010)
Constitutes the refereed proceedings of the 13th Conference of the Spanish Association for Artificial Intelligence, CAEPIA 2009, held in Salamanca, Spain, in November 2009, in conjunction with the Workshop on Artificial Intelligence Technology Transfer, TTIA 2009.